SOLUBILITY OF HYDROGEN IN OLIVINE: DEPENDENCE ON TEMPERATURE AND IRON CONTENT - Zhao Y.H.; Ginsberg S.B.; Kohlstedt D.L. (My University, 2004)
The solubility of hydrogen in Mg-Fe olivines as a function of temperature and iron concentration was investigated by hydrothermally annealing single crystals of synthetic forsterite and San Carlos olivine. Experiments were performed at temperatures between 1,273 and 1,573 K on samples with compositions between Fa0 and Fa16.9 under a confining pressure of 300 MPa in a gas-medium apparatus with oxygen fugacity, <![CDATA[$$ f_{{{\text{O}}_{{\text{2}}} }} $$]]>, buffered by the Ni:NiO solid-state reaction and silica activity, <![CDATA[$$ a_{{{\text{SiO}}_{2} }} $$]]>, buffered by the presence of enstatite. Hydroxyl concentrations were determined from infrared spectra obtained from polished thin sections in crack-free regions ≤50 µm in diameter. Hydroxyl solubility increases systematically with increasing temperature and with increasing iron content. Combined with published results on the dependence of hydroxyl solubility on water fugacity and pressure, the present results can be summarized by the relation <![CDATA[$$ C_{{{\text{OH}}}} = Af^{1}_{{{\text{H}}_{{\text{2}}} {\text{O}}}} \exp {\left[ { - {\left( {\Delta E^{{\text{o}}}_{{{\left\{ {} \right\}}}} + P\Delta V^{{\text{o}}}_{{{\left\{ {} \right\}}}} } \right)}/RT} \right]}\exp {\left( {\alpha X_{{{\text{Fa}}}} /RT} \right)} $$]]> with A=90±10 H/106Si/MPa, α=97±4 kJ/mol, <![CDATA[$$ \Delta E^{{\text{o}}}_{{{\left\{ {} \right\}}}} $$]]>=50±2 kJ/mol, and <![CDATA[$$ \Delta V^{{\text{o}}}_{{{\left\{ {} \right\}}}} $$]]>=(10.0±0.1)×10-6 m3/mol. The subscript {} indicates that hydroxyl ions are incorporated primarily as defect pairs, probably of the type <![CDATA[$$ {\left\{ {{\left( {{\text{OH}}} \right)}^{ \bullet }_{{\text{O}}} - {\text{V}}^{{''}}_{{{\text{Me}}}} - {\left( {{\text{OH}}} \right)}^{ \bullet }_{{\text{O}}} } \right\}}^{{\text{x}}} \equiv {\left( {2{\text{H}}} \right)}^{{\text{x}}}_{{{\text{Me}}}}. $$]]> Under similar thermodynamic conditions, the water content in olivine in the martian mantle and in olivine from gabbros may be as much as 5 to 25 times larger than in the less iron-rich olivine dominant in Earth's mantle.
Keywords: olivine